2010
DOI: 10.1088/0004-637x/722/2/1240
|View full text |Cite
|
Sign up to set email alerts
|

Transition From Regular to Chaotic Circulation in Magnetized Coronae Near Compact Objects

Abstract: Accretion onto black holes and compact stars brings material in a zone of strong gravitational and electromagnetic fields. We study dynamical properties of motion of electrically charged particles forming a highly diluted medium (a corona) in the regime of strong gravity and large-scale (ordered) magnetic field.We start our work from a system that allows regular motion, then we focus on the onset of chaos. To this end, we investigate the case of a rotating black hole immersed in a weak, asymptotically uniform … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
144
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 112 publications
(146 citation statements)
references
References 53 publications
2
144
0
Order By: Relevance
“…Since both of these systems were found to be nonintegrable, in which case the chaotic dynamics emerges, we subsequently focused on the dynamic properties of these orbits, trying to identify which parameters of the system trigger chaos. We found that within the off-equatorial lobes, the dynamics are mostly regular and chaos typically appears only when the energy of the particle is sufficiently increased to the level that corresponds to cross-equatorial confinements (Kopáček et al 2010a).…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…Since both of these systems were found to be nonintegrable, in which case the chaotic dynamics emerges, we subsequently focused on the dynamic properties of these orbits, trying to identify which parameters of the system trigger chaos. We found that within the off-equatorial lobes, the dynamics are mostly regular and chaos typically appears only when the energy of the particle is sufficiently increased to the level that corresponds to cross-equatorial confinements (Kopáček et al 2010a).…”
Section: Introductionmentioning
confidence: 86%
“…This work represents a natural extension of our previous studies (Kopáček et al 2010a;Kovář et al 2008Kovář et al , 2010) in which we considered dynamic properties of charged matter orbiting in the vicinity of massive objects. Our primary concern was to identify and investigate regions of a stable, off-equatorial motion.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations